Ultrafast high-temperature sintering of (Y0.2Dy0.2Er0.2Tm0.2Yb0.2)4Hf3O12 high-entropy ceramics with defective fluorite structure - Ye, Fuxing; Meng, Fanwei; Luo, Tianyuan; Qi, Hang (Journal of the European Ceramic Society, 2022)
An entropy-stabilized rare earth hafnate (Y0.2Dy0.2Er0.2Tm0.2Yb0.2)4Hf3O12 (5RH) with defective fluorite structure was successfully prepared by the emerging ultrafast high-temperature sintering (UHS) in less than six minutes. The 5RH ceramic possessed a higher thermal expansion coefficient (11.23 ×10−6/K, 1500 °C) and extremely low thermal conductivity (0.94 W/(m·k), 1300 ℃) owing to the larger lattice distortion of high-entropy materials. After high-temperature annealing at 1500 ℃, the 5RH showed extremely sluggish grain growth characteristics and excellent high-temperature phase stability, mainly attributed to the non-equilibrium sintering characteristic of the UHS and the sluggish diffusion effect of high-entropy materials. Therefore, (Y0.2Dy0.2Er0.2Tm0.2Yb0.2)4Hf3O12 has excellent potential as a next-generation thermal barrier coating material to replace traditional Y2O3 stabilized ZrO2. Finally, using the UHS to prepare high-entropy ceramics provides a new technique for fast-sintering and developing next-generation thermal barrier coating materials. •High-entropy (Y0.2Dy0.2Er0.2Tm0.2Yb0.2)4Hf3O12 ceramic is designed and successfully prepared by the emerging UHS.•The solid-phase synthesis and sintering densification of high-entropy ceramic bulks are simultaneously achieved by the UHS in less than six minutes.•The high-entropy (Y0.2Dy0.2Er0.2Tm0.2Yb0.2)4Hf3O12 ceramic shows great potential as new-generation thermal barrier coating material .•The emerging UHS provides ideas for the fast-sintering of ceramic materials and development of new materials.